Kajian Empiris Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia, dan Jumlah Penduduk Terhadap Ketimpangan Distribusi Pendapatan di Provinsi Jambi Tahun 2020-2024 - Dessy Anggraini; Beid Andriani Fitrianova; Khusnul Istiqomah; Abdurrahman Abdurrahman (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of economic growth, the human development index (HDI), and population on the income distribution gap in Jambi Province. Income distribution gap is an important indicator in assessing the success of a region's economic development. Although economic growth has increased, this is not always followed by income equality in society. This study uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS) of Jambi Province for the period 2020-2024. The analytical method used is panel data regression with model testing through the Chow test, the Hausman test, and the Lagrange Multiplier (LM) test. The results show that simultaneously, the variables of economic growth, HDI, and population have a significant effect on the income distribution gap. However, partially only the economic growth variable has no significant effect, while the HDI and population variables have a significant effect on the income distribution gap in Jambi Province for 2020-2024.